(untitled) (European Journal of Language and Literature, 2020)
The present paper aims at highlighting some cultural and cross-linguistic aspects of idioms causing miscommunication in language. Learning a foreign language shapes the language system of communication with its literal and figurative meanings. While the literal meaning is the direct reference of words or sentences to objects, the figurative sense is used for giving an imaginative description or a special effect. Gaining competence in language enrolls a good command of the figurative use of that language together with its frequent, spontaneous and appropriate use of idioms being an indicator of native or near native mastery of the language. When such command of a foreign language lacks then it gives rise to discrepancies in language, and idioms for the sake of truth become often subject to misconstrued utterances in a target language on the part of L2 learners. Using literal senses of words to trigger the recognition of idioms brings some potential problems. Thus, this article brings together the findings and insights of figurative aspect of English and Albanian language system and its cultural aspect to further the understanding of the phenomena of communicative failures and mismatches in language. The study seeks to analyze and present through a corpus analysis idiom occurrences of communication failure in both languages. A variety of figurative use of language is illustrated in certain contexts and situations to lighten up the usage of idiom mismatches in second language acquisition and provide the paper with rich examples as well.